Interpersonal communication everyday encounters - Wood, Julia T. (Wadsworth/Cengage Learning, 2013)
Award-winning author Julia T. Wood presents a pragmatic introduction to the concepts, principles, and skills of interpersonal communication?helping you build the skills you need to become a better communicator. You'll also read about such timely issues as the ethical challenges and choices that affect interpersonal communication, emotional intelligence and forgiveness, interracial relationships, safe sex, dealing with abuse from intimates, race-related differences between conflict styles, the power of language, and more! -- Product Description.